Electronic Keyboard Method - Palmer; Willard A, Manus; Morton and Lethco, Aamanda Vick (Alfred Publication, 1996)
Keyboardskole for begyndere.
Include Illustration
Keywords: Electronic keyboard (Synthesizer) -- Keyboard instruments